Virtual Reality Tata Ruang Letak Gedung Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta - Amani, Kholda Rafifah; Waathoni, Mahbubul; Adriansyah, Ahmad Fikri; Efendi, Yasin (Published by Institut Teknologi Pendidikan Indonesia, 2024)
Technology users can make it easier to carry out activities, in fact there are many applications that can help do various jobs or things without exception. One of these technologies is virtual reality. In developing virtual reality, a method is needed to create animation applications according to needs. The resulting display discusses the layout and facilities of the Jakarta Muhammadiyah University Faculty of Education Building. Users can also be helped to see the area and layout of the building without having to visit the location. This research method is research and development (R&D) using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The subjects of this research are visitors. Based on the results obtained from this research, 98% of presentations were categorized as very good and feasible. And its feasibility needs to be further studied in the long term.